Evaluation of sound environment in the Manufacturing and Marketing Company of glucose, starch and other corn byproducts. Cienfuegos, Cuba - Tamara Montenegro Calderón; Gloria Marilé Ávalos Ávalos; Alicia María Gómez Villarejo (Medisur)
Foundation: noise is included among the 5 risk factors of physical origin for health in the working environment. Objective: to determine if sound pollution at the Cienfuegos Manufacturing and Marketing Company of glucose, starch and other corn byproducts, exceeds maximum admissible values on NC 871/11 of Health Safety and Health at Work. Methods: a cross descriptive study at the Cienfuegos Manufacturing and Marketing Company of glucose, starch and other corn byproducts was conducted, on February 2018. A number of 287 persons were working, out of them 247 directly in production processes. Measurements of sound levels in the working areas were done according to the valid Cuban standard NC 19-01-14/83. Variables continues equivalent sound level, express in decibels (dB(A) and time of exposure in hours. To measure noise, it was used and integrative sonometer type 2. Measurements were done the during working hours. Results: in the steam generator, compressor boiler, grinding and generation areas, corn reception and cleaning, animal feed factory, dryers and centrifugal equipment noise levels exceed 90 db (a) of exposition. Conclusion: the levels of noise found exceed the admissible maximum which might produce harmful health consequences on workers therefore it is necessary to intervene this working environment